Does X‐ray imaging by GPC at emergency care access points in the Netherlands change patient flow and reduce ED crowding? A cohort study. Issue 2 (8th February 2018) - van den Bersselaar, D.L.C.M.; Maas, M.; Thijssen, W.A.M.H.
Abstract: Objective: Organizing out‐of‐hours emergency care is a challenge in many countries. In the Netherlands, general practitioner cooperatives (GPCs) and emergency departments (EDs) are increasingly working together, creating one emergency care access point (ECAP). This has redirected the majority of patients with musculoskeletal problems from the ED to the GPC in out‐of‐hours care, due to the treatment of self‐referrals by the general practitioner (GP). Only a minority of the GPs at ECAPs have the possibility to request X‐rays, and expanding these facilities could reduce patient presentations to the ED even more. The aim of our study was to explore patient flow and possible reductions in ED referrals at an ECAP with X‐ray facilities for GPs. Methods: This retrospective cohort study examines all patients that visited an ECAP at a general city hospital in the Netherlands and had an X‐ray imaging requested by the GPC between January 1, 2014 and December 31, 2014. General practitioner cooperatives could request X‐rays between 5 pm and 10 pm on weekdays and between 8 am and 10 pm during weekends. Recorded data included sex, age, number and type of X‐ray, X‐ray abnormalities, referral to the ED, and treatment. The annual number of patients presenting to the GPC and ED in 2014 were gathered. Patient outcome was stated negative when the X‐ray revealed no abnormality. Results: A total of 2243 patients received 2663 X‐ray examinations. The mean age was 31 years and 48% was male. A total of 1517 (68%) patients were treated at the GPC without an ED referral, a reduction of 4.5% of the annual ED patients. Conclusions: With a majority (68%) of the patients examined and treated at the GPC, X‐ray facilities at ECAPs will substantially reduce ED population, change patient flow, and have a positive effect on ED crowding. Implementing 24/7 X‐ray facilities at all ECAPs will further enhance these effects. Abstract : Organizing out‐of‐hours emergency care is an important challenge in many countries. EDs are confronted with crowding, while access to X‐ray facilities for general practitioners in out‐of‐hours care is minimal, leading to unnecessary referrals. This study showed that X‐ray facilities for general practitioner cooperatives in out‐of‐hours care will substantially reduce ED population, change patient flow, and have a positive effect on ED crowding.